2015
DOI: 10.1017/s0025315415000612
|View full text |Cite
|
Sign up to set email alerts
|

Under the radar: Sessile epifaunal invertebrates in the seagrassPosidonia australis

Abstract: Despite the current global decline in seagrass, sessile epifaunal invertebrates inhabiting seagrass ecosystems, particularly sponges and ascidians, have been poorly studied due to their taxonomic complexity. Understanding patterns of distribution of sessile epifaunal communities in seagrass meadows is an important precursor to determining the processes driving their distribution and species interactions. This study (1) identified the sponge and ascidian assemblage associated with Posidonia australis meadows an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…Variability in faunal community structure may be due to the fact that seagrass offers increased structural complexity (Gartner, Tuya, Lavery, & McMahon, ; Webster, Rowden, & Attrill, ) and habitat area (Attrill et al, ), refuge from predation and disturbance (Peterson, ), elevated food availability (Vizzini, Sarà, Michener, & Mazzola, ), altered sediment characteristics (Frost, Rowden, & Attrill, ), and increased retention of particles, such as propagules and particulate organic matter (Christoffer & Erik, ; Thorsten, ). In the current study, we recorded consistently higher abundances of sessile taxa (e.g., cnidarians, bryozoans) in areas containing seagrass, most likely as seagrass populations offer biogenic substrate for settlement and growth of these organisms (Balata, Nesti, Piazzi, & Cinelli, ; Demers, Knott, & Davis, ; Mabrouk, Ben Brahim, Hamza, & Bradai, ).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Variability in faunal community structure may be due to the fact that seagrass offers increased structural complexity (Gartner, Tuya, Lavery, & McMahon, ; Webster, Rowden, & Attrill, ) and habitat area (Attrill et al, ), refuge from predation and disturbance (Peterson, ), elevated food availability (Vizzini, Sarà, Michener, & Mazzola, ), altered sediment characteristics (Frost, Rowden, & Attrill, ), and increased retention of particles, such as propagules and particulate organic matter (Christoffer & Erik, ; Thorsten, ). In the current study, we recorded consistently higher abundances of sessile taxa (e.g., cnidarians, bryozoans) in areas containing seagrass, most likely as seagrass populations offer biogenic substrate for settlement and growth of these organisms (Balata, Nesti, Piazzi, & Cinelli, ; Demers, Knott, & Davis, ; Mabrouk, Ben Brahim, Hamza, & Bradai, ).…”
Section: Discussionsupporting
confidence: 52%
“…Bootstrapping and tmMDS based on Bray-Curtis distance matrices constructed from 4th-root transformed data Location C (Vizzini, Sarà, Michener, & Mazzola, 2002), altered sediment characteristics (Frost, Rowden, & Attrill, 1999), and increased retention of particles, such as propagules and particulate organic matter (Christoffer & Erik, 2000;Thorsten, 1998). In the current study, we recorded consistently higher abundances of sessile taxa (e.g., cnidarians, bryozoans) in areas containing seagrass, most likely as seagrass populations offer biogenic substrate for settlement and growth of these organisms (Balata, Nesti, Piazzi, & Cinelli, 2007;Demers, Knott, & Davis, 2015;Mabrouk, Ben Brahim, Hamza, & Bradai, 2015).…”
Section: Ta B L E 2 Glmms For Two Seagrass Bed Composition Metrics Isupporting
confidence: 52%
“…from Banyuwangi beach that inhabited a sandy substrate type associated with the T. hemprichii seagrass habitat. Furthermore, when we compared our results to other studies by Sivaleela et al (2013), Prabhakaran et al (2013), Demers et al (2015) and Ismet et al (2017) two genera: Calyspongia and Haliclona were also discovered in the other ecosystems with seagrass meadows (Table 2). The existence of conspicuous shallow-water sponges Calyspongia and Haliclona (Table 2) presumably indicates the suitability and adaptability of morphological characters to seagrass meadows i.e., a larger oscula of the sponges is presumed to provide greater protection and shelter against predation (Wulff 2008).…”
Section: Shallow Water Sponges and Seagrass Meadows Relationshipsupporting
confidence: 58%
“…and Toxochalina sp. sponges and Posidonia australis seagrass found in Australia (Demers et al 2015) and several other sponge and seagrass species found in Pulau Seribu, Indonesia (Ismet et al 2017). Due to the few studies conducted in the Indo-Pacific region despite its high sponge diversity, more explorations are needed in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Although fragmentation of seagrass habitats is not on the same spatial scale as fragmentation of terrestrial vegetation (see Saunders, Hobbs, & Margules, 1991), the ramifications might still be great. Fragmentation of seagrass meadows will have a range of subsequent effects on, for example, sediment stability and wave hydrodynamics (Colomer et al, 2017), nutrient cycling in sediments (Ricart, Dalmau, Pérez, & Romero, 2015), and invertebrate assemblages (Demers, Knott, & Davis, 2015;Hovel, 2003;Tanner, 2005). Some of the species associated with seagrasses are themselves threatened (e.g.…”
Section: Figurementioning
confidence: 99%